Keberadaan Kelompok Jamaah Tabligh dan Reaksi Masyarakat (Perspektif Teori Penyebaran Informasi dan Pengaruh) - Umdatul Hasanah (JURNAL INDO-ISLAMIKA, 2014)
Jamaah Tabligh is a transnational preaching movement that originated in India. The movement was introduced to Indonesia in 1970s and established Masjid Jami’ in Kebon Jeruk Jakarta as its headquarters. The members of Jamaah Tabligh referred to kitab Fadailul ‘A’mal which teaches innovations in Islamic propagations. Some of their preaching traditions included outdoor preaching (khuruj dan khillah) and the method to invite people to do good deeds (Jaulah). They have Amir as their leader and use the mosque as their center of da’wa activities. Using Diffusion of Information and Influence Theory, the article discusses the existence of the Jamaah Tabligh community and the public’s responses toward the community.